Three layers of abstraction: a conceptual framework for theorizing digital multi-sided platforms - Martin Poniatowski; Hedda Lüttenberg; Daniel Beverungen; Dennis Kundisch (Information Systems and e-Business Management, 2021)
The digital economy has brought about multi-sided platforms as superior configurations for value co-creation. However, the academic discourse on platforms is scattered across academic disciplines—including management, information systems, and economics. Based on a systematic literature review of 140 papers from nine disciplines, we inductively develop a framework that provides a conceptual point of reference for conducting boundary-spanning research on digital multi-sided platforms. Systematizing the identified concepts, we introduce three layers of abstraction: conceptualizing platforms as information systems, as systems for actor engagement, or as ecosystems. Our framework conceptualizes digital multi-sided platforms as nested hierarchies of systems that are shaped by, and in interaction with, their environment. This view focuses on designing IT artifacts, governance mechanisms, and strategies for platforms in terms of how they interact with their environment. Practitioners can use our insights to analyze, design, and manage platforms aimed at establishing a sustainable competitive advantage.
Keywords: 650; Multi-sided platform; Digital platform; Conceptual framework; Literature review